Hydrogen evolution from glycerol aqueous solution under aerobic conditions over Pt/TiO2 and Au/TiO2 granular photocatalysts. Issue 93 (4th November 2016) - Sakurai, Hiroaki; Kiuchi, Masato; Heck, Claire; Jin, Tetsuro
Abstract : Hydrogen was efficiently evolved from glycerol aqueous solution upon vertical photoirradiation of a Pt/TiO2 or Au/TiO2 bed under aerobic conditions. Abstract : Hydrogen was efficiently evolved from glycerol aqueous solution upon vertical photoirradiation of a Pt/TiO2 or Au/TiO2 bed under aerobic conditions. Granular photocatalysts were easily deposited, leading to high H2 selectivity (80–95%), whereas glycerol oxidation with CO2 evolution became dominant when suspended powder photocatalysts were used.